An international probabilistic risk assessment of acute dietary exposure to pesticide residues in relation to codex maximum residue limits for pesticides in food. (March 2021) - Crépet, Amélie; Luong, The Minh; Baines, Janis; Boon, Polly E.; Ennis, Julie; Kennedy, Marc; Massarelli, Isabelle; Miller, David; Nako, Steve; Reuss, Rainer; Yoon, Hae Jung; Verger, Philippe
Abstract: The Joint Food and Agriculture Organization of the United Nations (FAO)/World Health Organization (WHO) Meeting on Pesticide Residues (JMPR) is the scientific body assessing the risk of exposure to pesticide residues in food and proposing maximum residue levels (MRLs) to the Codex Alimentarius Commission. When agreed, these levels become Codex maximum residue limits (CXLs), to be potentially adopted by countries and used as references for trade disputes. In the context of a review of models and methodologies used by JMPR to assess acute dietary exposure to pesticide residues, WHO performed a probabilistic dietary exposure assessment, which takes into consideration actual measured pesticide residues and agricultural practices, to serve as a "real world"–based estimate of the actual acute dietary exposure to 38 pesticides in eight countries. The results show the absence of appreciable risk for all countries and populations considered, even with the conservative scenario based on 100% usage of pesticides in all foods. Moreover, our results indicate that, with only a few exceptions, most of the CXLs established by the Codex Alimentarius Commission would provide a high level of protection even if risk managers do not request a specific level of protection from risk assessors. Highlights: WHO performed a probabilistic assessment of the acute dietary exposure to 38 pesticides. Food consumption data from eight countries and more than 70 000 individuals were used. More than 2 million results from pesticide monitoring programs were used. There is no appreciable risk from acute dietary exposure to pesticides in the countries and populations considered. Most Codex maximum residue limits for pesticides provide a high level of protection.